Toxins in Drug Discovery and Pharmacology - Steve Peigneur (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Venoms from marine and terrestrial animals (cone snails, scorpions, spiders, snakes, centipedes, cnidarian, etc.) can be seen as untapped cocktails of biologically active compounds that are being increasingly recognized as a new emerging source of peptide-based therapeutics. Venomous animals are considered to be specialized predators that have evolved the most sophisticated peptide chemistry and neuropharmacology for their own biological purposes by producing venoms that contain a structural and functional diversity of neurotoxins. These neurotoxins appear to be highly selective ligands for a wide range of ion channels and receptors. Therefore, they represent interesting lead compounds for the development of analgesics, anti-cancer drugs, drugs for neurological disorders such as multiple sclerosis, Parkinson' s disease, Alzheimer' s disease, and other therapeutics. This Special Issue of Toxins aims to provide a comprehensive look at toxins and toxin-inspired leads and will focus on the mechanisms of action, structure-function relationships, and evolution of pharmacologically interesting venom components, including the most recent developments related to the emergence of venoms as an underutilized source of highly evolved bioactive peptides with clinical potential.